Consensus, terrorism and peace - The role of Malaysia’s media to promote world unity in the post-September 11th scenario - Jaganathan Marimuthu, (Faculty of Social Sciences and Humanities, UKM,Bangi, 2007)
September 11, 2001 has brought to the fore the issue of international terrorism calling for a global consensus to bridge ideological, cultural and political gaps between the West and East. Given that Malaysia is characterized by a blend of East and West as well as the status of a progressive Muslim nation, the key question posed in this paper is whether Malaysian media are able to build the much needed global consensus in a multilateral context, particularly amongst South East Asian countries. This calls for an examination of the Malaysian media culture as, for instance, through a random survey of media reports, commentaries, and letters from the Malaysian mainstream media following the two tragic events of 9-11 and the US-led strikes against Afghanistan. The study looks at both articles and letters to assess whether the government and the journalists’ views are similar to those of the population at large. The results show that while the mainstream media in Malaysia can enlighten the West on perceived injustices leading to grievances, they are also in a unique position to initiate a reform of moderate and liberal thinking in the Islamic world. The emergent moderate and balanced stances as highlighted in this study lead to the conclusion that the Malaysian media have the scope of fostering greater understanding across religions, cultures and societies, the very foundation needed both to establish a consensus with regard to international terrorism and to build a world of peaceful coexistence for future generations